Estimation of Surabaya River Water Quality Using Kalman Filter Algorithm - Ali Masduqi; Erna Apriliani (IPTEK The Journal for Technology and Science, 2008)
According to previous studies on Surabaya River water, quality of this river water was very bad or on polluted condition. This conclusion was based on monitoring data of water quality at several monitoring points. Because of river water quality is a fluctuative condition, many monitoring data are needed. While, monitoring of Surabaya River water quality was done routinely at nine monitoring points. Amount of the monitoring point is not enough when data will be used for determining water quality condition. For this reason, it is need to develop a method to estimate overall river water quality based on a little amount of data. One of estimation method is Kalman filter, an algorithm that combines a model and a measurement. The experiment of Kalman filter algorithm was conducted. The results were accurate and closely with a measurement. Based on the results, application of Kalman filter algorithm will help to predict water quality for the future and to estimate overall water quality along of river, although amount of measurement data is a little.